Management of proximal lacrimal obstructions: a rationale - Quaranta‐Leoni, Francesco M.; Fiorino, Maria Grazia; Serricchio, Fabio; Quaranta‐Leoni, Flavia (Acta ophthalmologica (Oxford, England), 2021)
Purpose To identify a rationale for correct surgical treatment of proximal lacrimal obstructions. Methods Retrospective review of 775 consecutive patients (974 eyes) with proximal lacrimal obstructions, operated on with customized surgery by a senior surgeon (FMQL) from January 2003 to December 2018. Results In case of punctal stenosis, punctoplasty was as effective as punctal dilatation with monocanalicular or bicanalicular stent (p > 0.05). In proximal canalicular obstructions, failure rate of dacrocystorhinostomy with retrograde intubation (R‐DCR) was significantly higher in case of false inferior passage creation than in case of no false passage creation (p = 0.02). In mid‐canalicular obstructions failure rate of R‐DCR was 41.3%, and bypass surgery with Jones tube at second stage was likely. Trephination and monocanalicular intubation, performed in selected cases, had a failure rate respectively of 16.6% and 21.7% in mid and distal canalicular obstructions. Canaliculodacryocystorhinostomy (CDCR) was successful in 77% of cases of proximal common canalicular obstruction. Bypass surgery is the treatment of choice in case of no residual patency, and rates of tube extrusion were significantly reduced with the use of StopLoss Jones tubes (SLJT) (1.7%) with respect to standard tubes (12%), (p = 0.04, Fisher’s exact test). Conclusion Patient history and accurate diagnosis of the site of obstruction are essential for a correct surgical choice. Less invasive techniques as trephination and intubation may be effective, but should be reserved to patients with no associated lower lacrimal obstruction. Further studies require specific randomized clinical trials, and a standardized protocol adopted by different clinical centres.